2014
DOI: 10.1016/j.bone.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional analysis of subchondral cysts in hip osteoarthritis: An ex vivo HR-pQCT study

Abstract: Introduction Subchondral cysts are deeply related to the pathogenesis of osteoarthritis (OA), but the factors contributing to cyst formation are not well known. A three-dimensional analysis of subchondral cysts at the micro-structural level was conducted using high-resolution peripheral quantitative CT (HR-pQCT), and their relationships with cartilage attrition and subchondral bone microstructure were investigated. Methods Femoral heads extracted from ten female patients with hip OA were scanned using HR-pQC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 25 publications
3
32
0
Order By: Relevance
“…We observed subchondral bone cysts in all of OA samples, which are consistent with other reports on OA hip (Chiba et al, 2014). These fluid-filled voids in subchondral bone, which are typically referred to as "subchondral bone cysts, " are normally reported in OA patients.…”
Section: Discussionsupporting
confidence: 91%
“…We observed subchondral bone cysts in all of OA samples, which are consistent with other reports on OA hip (Chiba et al, 2014). These fluid-filled voids in subchondral bone, which are typically referred to as "subchondral bone cysts, " are normally reported in OA patients.…”
Section: Discussionsupporting
confidence: 91%
“…It also allows us to analyze the microstructure of bone samples ex vivo, similar to micro-CT [8]. While micro-CT is mainly used for small experimental animals, HR-pQCT can be used for large bone samples, such as the human cadaver spine [9][10][11][12][13][14][15][16]. It has been reported that HR-pQCT results in fewer errors in measurements of bone morphology compared to the histological method [17].…”
Section: Introductionmentioning
confidence: 99%
“…With regards to quantifying cyst presence, this was completed using a custom semi-quantitative approach combining methods from Kornaat et al 5 and results from Chiba et al 6 . A single researcher (JDJ) retrospectively evaluated all CT scans (mainly sagittal and coronal reconstructions) for cyst presence, size and number.…”
mentioning
confidence: 99%
“…With the assumption that cysts are predominantly spherical in shape, segmented areas were converted to equivalent cyst diameters and volumes. Individual cyst sizes were classified as: none, 0e1.25 mm diameter, 0e1 mm 3 volume, as per Chiba et al 6 ; mild, 1.25e2.5 mm diameter, 1e8 mm 3 volume; moderate, 2.5e5 mm diameter, 8e65 mm 3 volume; large, >5 mm diameter, >65 mm 3 volume, as per Kornaat et al 5 . In instances where there were multiple cysts, the volumes of individual cysts were summed and total cyst volume dictated the specific grouping.…”
mentioning
confidence: 99%
See 1 more Smart Citation